2023
DOI: 10.3390/vaccines11040822
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences of the Effect of Vaccination on Perceptions of COVID-19 and Mental Health in Japan

Abstract: Vaccination has been promoted to mitigate the spread of the coronavirus disease 2019 (COVID-19). Vaccination is expected to reduce the probability of and alleviate the seriousness of COVID-19 infection. Accordingly, this might significantly change an individual’s subjective well-being and mental health. We observed the same individuals on a monthly basis from March 2020 to September 2021 in all parts of Japan. Then, large sample panel data (N = 54,007) were independently constructed. Using the data, we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…(2021) found that those who were fully vaccinated were less likely to practice social distancing based on representative samples of 12 countries. In addition, Yamamura et al (2023), Bernal et al (2021) and Hunter and Brainard (2021) observed a small but significant increase in infection rates during the first few weeks following the first dose take-up of vaccines in Japan, the U.K., and Israel, respectively. Researchers speculated that the results reflected lower compliance with protective behaviors (Independent SAGE, 2021;Rubin et al, 2021;SPI-B, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…(2021) found that those who were fully vaccinated were less likely to practice social distancing based on representative samples of 12 countries. In addition, Yamamura et al (2023), Bernal et al (2021) and Hunter and Brainard (2021) observed a small but significant increase in infection rates during the first few weeks following the first dose take-up of vaccines in Japan, the U.K., and Israel, respectively. Researchers speculated that the results reflected lower compliance with protective behaviors (Independent SAGE, 2021;Rubin et al, 2021;SPI-B, 2021).…”
Section: Discussionmentioning
confidence: 97%